2020
DOI: 10.1097/eja.0000000000001227
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output estimation by pulse wave analysis using the pressure recording analytical method and intermittent pulmonary artery thermodilution

Abstract: BACKGROUND Invasive pulse wave analysis is used in peri-operative settings to estimate cardiac output (CO). The ‘pressure recording analytical method’ (PRAM) implemented in the MostCareUp CO monitor is an invasive pulse wave analysis method using high-frequency sampling and analysis of the pulse wave to directly estimate the arterial impedance as a key variable of the proprietary CO estimation algorithm. OBJECTIVE To compare CO estimated by PRAM (PRAM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…CI was measured using the MostCareUp system (Vygon), a system for invasive pulse wave analysis. [7][8][9] Anesthesiologists were blinded to these CI measurements. Dynamic response of the arterial catheter/tubing/transducersystem was confirmed before study measurements with fast-flush tests; we also confirmed that transducers were correctly leveled and zeroed.…”
Section: Study Measurementsmentioning
confidence: 99%
“…CI was measured using the MostCareUp system (Vygon), a system for invasive pulse wave analysis. [7][8][9] Anesthesiologists were blinded to these CI measurements. Dynamic response of the arterial catheter/tubing/transducersystem was confirmed before study measurements with fast-flush tests; we also confirmed that transducers were correctly leveled and zeroed.…”
Section: Study Measurementsmentioning
confidence: 99%
“…Additionally, an automated waveform filter, which assists the user in ensuring an optimal quality of the arterial pulse wave, is integrated in PRAM. PRAM has been investigated in different clinical settings and patient cohorts with mostly promising results 6,8 but there is not enough evidence to transfer the results of PRAM-CO in critically ill patients to vvECMO patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 It is implemented in the MostCareUp monitoring system (Vygon, Ecouen, France) and has been validated for CO measurements in adult surgical and critically ill patients before. [6][7][8] We aimed to compare CO measurements by PRAM (PRAM-CO; test method) with CO measurements by transthoracic echocardiography (TTE) (TTE-CO; reference method) in patients with vvECMO therapy. We thus performed a prospective clinical method comparison study to test the hypothesis that the agreement between PRAM-CO and TTE-CO is clinically acceptable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MostCare system (Vygon, France) is currently the only commercially available minimally invasive uncalibrated pulse wave analysis system, and its CO values showed good agreement with those obtained by pulmonary artery thermodilution. 25 It uses the pressure recording analytical method algorithm to continuously estimate CO. The algorithm identifies specific ephemeral points of instability of the arterial blood pressure waveform that are mainly due to wave reflections by analyzing the arterial blood pressure waveform in a very high resolution.…”
Section: Minimally Invasive Uncalibrated Pulse Wave Analysismentioning
confidence: 99%